Achieving Lower Nitrogen Balance and Higher Nitrogen Recovery Efficiency Reduces Nitrous Oxide Emissions in North America's Maize Cropping Systems - Omonode, Rex A.; Halvorson, Ardell D.; Gagnon, Bernard; Vyn, Tony J. (Frontiers in Plant Science, 2017)
Few studies have assessed the common, yet unproven, hypothesis that an increase of plant nitrogen (N) uptake and/or recovery efficiency (NRE) will reduce nitrous oxide (N2O) emission during crop production. Understanding the relationships between N2O emissions and crop N uptake and use efficiency parameters can help inform crop N management recommendations for both efficiency and environmental goals. Analyses were conducted to determine which of several commonly used crop N uptake-derived parameters related most strongly to growing season N2O emissions under varying N management practices in North American maize systems. Nitrogen uptake-derived variables included total aboveground N uptake (TNU), grain N uptake (GNU), N recovery efficiency (NRE), net N balance (NNB) in relation to GNU (NNB(GNU)) and TNU (NNB(TNU)), and surplus N (SN). The relationship between N2O and N application rate was sigmoidal with relatively small emissions for N rates <130 kg ha-1, and a sharp increase for N rates from 130 to 220 kg ha-1; on average, N2O increased linearly by about 5 g N per kg of N applied for rates up to 220 kg ha-1. Fairly strong and significant negative relationships existed between N2O and NRE when management focused on N application rate (r2 = 0.52) or rate and timing combinations (r2 = 0.65). For every percentage point increase, N2O decreased by 13 g N ha-1 in response to N rates, and by 20 g N ha-1 for NRE changes in response to rate-by-timing treatments. However, more consistent positive relationships (R2 = 0.73-0.77) existed between N2O and NNB(TNU), NNB(GNU) and SN, regardless of rate and timing of N application; on average N2O emission increased by about 5, 7, and 8 g N respectively, per kg increase of NNB(GNU), NNB(TNU), and SN. Neither N source nor placement influenced the relationship between N2O and NRE. Overall, our analysis indicated that a careful selection of appropriate N rate applied at the right time can both increase NRE and reduce N2O. However, N2O reduction benefits of optimum N rate-by-timing practices were achieved most consistently with management systems that reduced NNB through an increase of grain N removal or total plant N uptake.